Translation, adaptation, and contribution to the validation of the Warwick–Edinburgh Mental Well-Being Scale for the Portuguese population - Figueiredo, Sofia (2022)
Introduction The concept of mental well-being has gained more prominence internationally as a crucial aspect of health, with an impact on functionality. Therefore, there is a need to have validated measures that can assess the Portuguese population’s mental well-being. Objective: To translate, culturally adapt and contribute to the validation of the Warwick–Edinburgh Mental Well-Being Scale, which assesses subjective and psychological mental well-being, for the Portuguese population. Material and Methods: After the approval of the Portuguese translation by an expert panel, the scale was administered to 1728 subjects from Porto’s metropolitan area, along with the Pemberton Happiness Index, to analyse the criterion validity. Cronbach’s alpha was used to analyse the internal consistency, and an exploratory factor analysis was used for the construct validity. Both scales were administered twice to 39 participants, with the second survey approximately one week after the first survey was conducted, to analyse the test–retest reliability. Results: A Cronbach’s alpha of 0.91 was obtained, suggesting very good internal consistency. The factor analysis confirmed the unidimensionality of the scale, since all items saturated into one single factor, similar to previous validations. There was a high correlation between the WEMWBS and the scale used as a criterion measure, with r=0,75. The test–retest reliability had a high correlation, with r=0,77. Conclusion: The values obtained in this first validation study of the WEMWBS for the Portuguese population are close to those obtained in the original validation and thus can be considered to have a legitimate and important contribution to the validation of the scale.